Have We Solved Glottis Segmentation? Review and Commentary - Kist, Andreas; Döllinger, Michael (Journal of Voice, 2024)
Quantification of voice physiology has been a key research goal. Segmenting the glottal area to describe the vocal fold motion has seen increased attention in the last two decades. However, researchers struggled to fully automatize the segmentation task. With the advent of deep learning, fully automated solutions are within reach and have been proposed. Are we then done here? This commentary highlights the open construction sites and how glottis segmentation can be still of scientific interest in this decade.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Deep learning—Glottis segmentation—Vocal folds—Quantification—Glottal area—Image processing—Image analysis—Deep neural networks